2018
DOI: 10.1590/abd1806-4841.20185788
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patients diagnosed with primary cutaneous melanoma in the last six years in Hospital Erasto Gaertner: epidemiologic profile

Abstract: BACKGROUNDMelanoma is one of the conditions with greater increase in incidence worldwide in recent decades. It is a skin cancer with potential high lethality and predominates in Caucasian adults. Treatment of primary cutaneous melanoma is essentially surgical and search for sentinel lymph node can modify the aggressiveness of the treatment.OBJECTIVETo analyze the epidemiological profile of patients diagnosed with primary cutaneous melanoma, histopathological features and compare with literature data.METHODSThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
(12 reference statements)
0
3
1
5
Order By: Relevance
“…In a study conducted in São Paulo by Melo et al ( 2018), (21) a slight predominance of cases was found among females (51.9%). Furthermore, in 2020, Wainstein et al (22) showed a majority of cases among women (57%), in addition to studies carried out in Brusque, SC (12) and Curitiba, PR (23) that also detected predominance of women (56.6% and 58.9%, respectively).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a study conducted in São Paulo by Melo et al ( 2018), (21) a slight predominance of cases was found among females (51.9%). Furthermore, in 2020, Wainstein et al (22) showed a majority of cases among women (57%), in addition to studies carried out in Brusque, SC (12) and Curitiba, PR (23) that also detected predominance of women (56.6% and 58.9%, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…It is possible to find divergent data in the literature regarding this variable. According to Lima et al (2015) (12) and to Foiato et al ( 2018), (23) the trunk was also the most common location of primary tumors in studies carried out in the cities of Brusque and Curitiba, respectively. In contrast, Vazquez et al (2015) (29) demonstrated that the most prevalent location in Brazilian women was the lower limbs (36.3%).…”
Section: Discussionmentioning
confidence: 98%
“…Em Minas Gerais, o lentigo maligno foi o mais comum. Esses dados mostram variação de acordo com as características populacionais 21,24 .…”
Section: Discussionunclassified
“…Em relação ao estadiamento, 83% dos extensivos superficiais e 91% dos lentigos malignos eram T1. Esse dado vai ao encontro de estatísticas de países de primeiro mundo, como os Estados Unidos, Suíça e Holanda, onde foram encontrados tumores finos em cerca de dois terços dos pacientes 14,18,24 . Em contrapartida, em estudo realizado por Vilanova et al 9 , no Nordeste brasileiro, foram encontrados apenas 27,6% de melanomas finos, com espessura média dos tumores de 8,8 mm e alta prevalência do subtipo nodular, retratando atraso no diagnóstico e piora no prognóstico dos pacientes 2,19,20,24 .…”
Section: Discussionunclassified
See 1 more Smart Citation